Clinical profiling and use of loop-mediated isothermal amplification assay for rapid detection of Mycobacterium tuberculosis from sputum - Poudel, A; Pandey, BD; Lekhak, B; Rijal, B; Sapkota, BR; Suzuki, Y (Kathmandu University Medical Journal, 2010)
Background: Tuberculosis is a global health problem and the situation is worsening with newer incidences of drug resistance and HIV association. Diagnosis of tuberculosis can be done by many methods and test, culture of sputum being the ideal one. Nucleic acid amplification (NAA) assay are more time efficient one, that amplify and detect specific nucleic acid sequences allows rapid, sensitive and specific detection of M. tuberculosis in sputum samples. Objectives: The present study intends to compile the clinical presentations of the pulmonary tuberculosis (PTB) patients and to evaluate the efficacy of in-house loop-mediated isothermal amplification (LAMP) in detecting Mycobacterium tuberculosis in sputum samples by comparing with microscopy and culture. Materials and methods: Two hundred two sputum samples were collected from 202 patients at National Tuberculosis Center, Bhaktapur, Nepal. Complete clinical profiling, epidemiological data and record on BCG vaccination were noted and the samples were subjected for microscopy, culture and in-house LAMP with six primers specific for 16S RNA gene of Mycobacterium tuberculosis. Result: Of the 176 cases of clinical profiling, productive cough was most common symptom in 147 (83.52%), followed by chest pain 136 (77.27%), fever 133 (75.56%) and haemoptysis 61 (34.66%). There was a statistically significant association between BCG vaccination and development of TB (Χ2=5.33, P=0.02). Of 202 cases, 115 (56.93%) were chest X-ray positive, 101(50%) were direct smear-positive and 100 (49.51%) were culture positive. LAMP had a sensitivity of 97% and specificity of 94.12% while comparing with culture. In addition, its sensitivity and specificity were 91.09% and 89.11% respectively with reference to microscopy. Conclusion: As in our previous study, overall, the result of present study further confirms that the in-house LAMP is a simple, rapid, sensitive and specific DNA amplification technique for PTB diagnosis. Because of rapidity of microscopy and specificity of culture, in-house LAMP assay can be used as a very powerful and useful supplementary tool with complete clinical profiling of the patients for rapid diagnosis of TB in both AFB-positive and negative cases who are suspected as PTB in disease endemic country like Nepal. Key words: clinical profiling; Sputum; DNA; LAMP; M. tuberculosis; Nepal DOI: 10.3126/kumj.v7i2.2701 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 109-114